IMPLEMENTASI MEDIA KARTU AKHLAK DALAM MENANAMKAN AKHLAKUL KARIMAH DI TPQ AL-HIDAYAH MENJANGAN - Kharismatul Khasanah; Abdan Syakuro; Zahwa Ardhinia Naisa; Sasa Refiatul Alfianti; Ferida Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of character-building flashcards in instilling good moral values in early childhood students at TPQ Al-Hidayah Menjangan. This study employs a qualitative approach using field research. The research subjects consist of TPQ students and teachers who were purposively selected based on their involvement in the character education learning process. Data collection was conducted through observation, direct practice of applying the moral character card media, and documentation. Observation was used to observe the children’s responses and engagement; direct practice was conducted through activities involving the introduction, categorization, and simple evaluation of cards depicting praiseworthy and blameworthy behaviors; while documentation was used to support the field data. Data were analyzed using qualitative descriptive methods through the stages of data reduction, data presentation, and drawing conclusions. The research results indicate that the moral values card medium is effective in enhancing children’s enthusiasm, active engagement, and understanding of akhlakul karimah values. Children can identify and distinguish between virtuous behaviors such as honesty, politeness, and respecting parents, as well as undesirable behaviors such as lying and disobedience. This medium also contributes to cognitive, social, and interpersonal intelligence development through play-based learning. These findings suggest that visual-interactive media are more effective in the internalization of moral values compared to conventional methods. Factors supporting implementation include teachers setting a good example and engaging teaching materials, while the main obstacles are differences in children’s abilities and limited attention spans.